Investment Decision Making in Digital Business Using Tsukamoto Fuzzy Logic - Fuad, Muhammad; Wattimena, Fegie Yoanti; Rizani, Ahmad; Yuswardi (International Journal Software Engineering and Computer Science (IJSECS), 2023)
This research investigates the application of Tsukamoto's Fuzzy Logic in investment decision making in a digital business context. By integrating human knowledge and numerical data, this method seeks to overcome the challenges of complexity and uncertainty that often arise in the fast-changing digital business environment. Through analysis of case studies and interviews with industry practitioners, this study identifies the steps for implementing effective Tsukamoto Fuzzy Logic, including the formation of fuzzy variables, determination of membership functions, application of fuzzy rules, and defuzzification processes. The results of Tsukamoto's Fuzzy Logic calculations are applied to digital investment cases, providing an overview of investment quality based on various input variables. This research shows that this method can produce a holistic and informative approach in making investment decisions. In addition, the diverse participation of practitioners in various regions provides valuable insights in dealing with the uncertainties of digital business. In this challenging digital era, this research provides guidance for decision makers in dealing with the complexities of a dynamic business environment.